From Lenin’s Imperialism to the Empire of Hardt and Negri: “Superior Phases” of Eurocentrism - Grosfoguel, Ramón; University of California, Berkeley (Editorial Pontificia Universidad Javeriana, 2008)
This article presents a critique of the book  Empire by Hardt and Negri. The article is based on the author’s investigation of the decolonialization of the paradigms of economy-politics. The first part of the essay is a summary of the basic concepts used in the book, such as coloniality, body politics and geopolitics of knowledge, as well as the colonial difference. Then the essay continues with a critical discussion of Lenin’s linear, eurocentric vision in regards to “imperialism”, and Marx’ stage vision in regards to the processes of “accumulation of capital”. Finally, the article discusses how Hardt and Negri’s book Empire is written with a linear, eurocentric narrative that conceals coloniality of power processes that take place on a world-wide scale